The talent development of NAMCYA piano winners implications for enhancing giftedness in music - Cruz, Juvy A. Santos (Quezon City College of Music, University of the Philippines Diliman, 2014)
This a descriptive study of NAMCYA piano winners in terms of their talents, outlooks, experiences; their home, school, and community life; their music, and the people and events that influenced their outstanding performance as musicians. The objective is to gather qualitative data that may be useful in enhancing giftedness in music and nurturing the special ability of gifted learners who are musically-inclined.
Thesis (Master in Music)--University of the Philippines,Diliman
Keywords: Musical ability; Gifted children -- Identification